That photograph: serial killer as modern celebrity - Cummins, Ian (Critiquing violent crime in the media, 2021)
In October 1965, Ian Brady and Myra Hindley were arrested for the murder of seventeen-year-old Edwards Evan. Since that date, the Moors Murders case has never disappeared from popular and media culture. Brady and Hindley became icons of evil, a reference point against which future crimes were measured. The Moors Murders case has become an archetype of mediatised murder. The photographs taken of Brady and Hindley at Hyde Police Station in Greater Manchester have appeared countless times in media reporting of Moors Murders and other cases. This chapter will use an analysis of the famous photographs taken of Brady and Hindley at the time of their arrest as a basis for the exploration of the modern celebrity status of the serial killer. It will then explore the pivotal role of that photograph in the construction of Hindley as ‘a monster’.